Surfactant-assisted fabrication of room-temperature self-healable dielectric elastomer toward actuation application. (1st April 2022) - Nie, Run-Pan; Tang, Wen-Bin; Li, Yue; Jia, Li-Chuan; Xu, Ling; Huang, Hua-Dong; Lei, Jun; Li, Zhong-Ming
Abstract: Dielectric elastomers are widely used for actuation applications in emerging domains such as tunable optics, tactile displays and soft robotics. However, dielectric elastomer actuators (DEAs) are prone to suffering from electrical or mechanical damage under the conditions of high operating voltage and mechanical stress, leading to a short service time and a low reliability. To address these issues, we in this work made an attempt to facilely develop a self-healable dielectric elastomer that combines high stretchability, dielectric properties, large actuation and effective repairing of mechanical and electrical failure by constructing multitype noncovalent interactions under surfactant assistance. It is demonstrated that the as-prepared elastomer possesses good healability at room temperature. After mechanical injury, a gentle pressure can initiate the recovery of damaged region, and the elastomer film could be subjected to a huge strain of 750% after healing for 24 h. In particular, this as-fabricated DEA that suffered from accidental or repetitive breakdown could still be re-actuated stably without significantly decreasing its actuated strain after quick healing (∼5 min). It is also found that embedding a fluoroelastomer with a fluorosurfactant can achieve larger deformation (tan α = 0.57 at 30 MV/m) due to the improved electromechanical properties. Our strategy for achieving self-healing feature and high actuation performance is favorable for extending lifetime, strengthening damage tolerance and lowering excitation voltages required for the DEAs. Graphical abstract: Image 1 Highlights: A self-healable dielectric elastomer with multitype dynamic interactions is prepared. Mechanically cut damage can be quickly and effectively healed at room temperature. Dielectric elastomer actuator can be re-actuated after accidental breakdown. The improved electromechanical performance leads to desirable deformation.